JAJAR LEGOWO PLANTING SYSTEM AS THE STRATEGY ON CLIMATE CHANGE ADAPTATION (CASE STUDY IN SRIGADING VILLAGE, LAWANG DISTRICT, MALANG) - Elis Siti Toyibah; Sujarwo Sujarwo; Condro Puspo Nugroho (Socio-Economics/Agribusiness Department, 2016)
Most Indonesian people need rice as their staple food. East Java is one of provinces in Indonesia which has large potential of rice farming productivity. One area in East Java Province which played role as central rice production is Lawang District. Moreover, Srigading Village, the location of this research, is one village in Lawang District that livelihood of the most people in the area is farmer. Farmers in Srigading Village often face crops failure because the field was affected by climate change. The purpose of this research is to analyze the application of jajar legowo planting system as an effort to increase farmer income and as the strategy to the climate change adaptation. Data type that used in this research is cross sectional data mostly generated using interview with the respondents. Data in this research was rice farming data in one planting season which is from February to June. T-test is applied to test the average result between jajar legowo planting system and conventional planting system. The results show that Jajar Legowo planting system has better performance, considering production and less cost applied, compared to the conventional planting system.